"Bicara Buku: Prof. Dato Dr Rahmat Mohamad" - UiTM, Faculty of Law (Faculty of Law, 2020)
"Bicara Buku Bersama YBhg Prof. Dato Dr. Rahmat Mohamad', a talk by the author himself, who is also the Deputy Vice Chancellor ( Industry, Community, Alumni and Entrepreneurship Network), Universiti Teknologi MARA was held on 25 February 2020. The event was hosted by Penerbit UiTM and was held at Auditorium 2, Faculty of Law, UiTM Shah Alam. The book that was the subject matter of the talk was titled "Asian and African Views on International Law". The event was attended by Part l students of UiTM Law, Asasi law students from Dengkil and some lecturers and staff. Prof. Dato Dr. Rahmat shared his working experiences, moments and challenges as the Secretary General of the Asian African Legal Consultative Organization (AALCO) in New Delhi, India. It was a good exposure and an eye opener for the students. Prof. Dato Dr. Rahmat emphasised on the importance of unity between the people of Africa and Asia, and how vital it is to secure peace, harmony and cooperation among these two continents and other nations around the world. On a lighter note, the talk also highlighted Prof. Dato Dr. Rahmat's fondness for Indian cuisine and how the people he met were very friendly and welcoming. In summary, the talk produced curiosity and interest in many of the attendees, as well as sparking laughter now and then as Prof. Dato Dr. Rahmat was able to make it not only educational but entertaining too. After the talk ended, Prof. Dato Dr. Rahmat answered questions posed by some students. Prof. Dato Dr. Rahmat motivated and inspired the students when he talked about how much he enjoyed working in a country outside Malaysia and how a person will know more about humankind when he travels to places that he has never set foot in before.